Agile working and its potential effects on urban planning - Wadia, Nazeefah (My University, 2018)
Agile working in the workplace has increasingly become part of modern work practices to accommodate the needs of employers and employees. It is a transformational concept that allows businesses the possibility to eliminate barriers by working smarter and allowing the business to operate in a manner that is efficient, effective and responsive to the current market while ultimately ensuring increased levels of client satisfaction and overall sustainability. The purpose of this research is to understand how alternative commercial working practices may have an impact on urban planning, which include transportation usage, the link between public and private environments and policy implementation. The research will take an exploratory research design approach to the study as the subject of agility in the workplace and its impacts on the urban environment and urban planning have very limited existing research. Although it is impossible to predict future preference of work styles it is possible to consider a number of contributing factors that could assist in providing efficient and sustainable environments, both public and private, for the future. It is imperative that planners and developers address and act upon the potential opportunities to ensure that cities remain attractive to a variety of users. In addition, cities should leverage their uniqueness and provide a balance of amenities to ensure current environments are liveable, sustainable, integrated and address the needs of the public.
A research report submitted to the Faculty of Engineering and the Built Environment at the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Development Planning, in the year 2018